Adaptive Neuro-Controller for three-axes attitude control of innovative satellite - Siti Maryam, Sharun; Mohd Yusoff, Mashor, Prof. Dr.; M. N. Norhayati; W. N. Hadani; Sazali, Yaacob, Prof. Dr. (Science Academy Publisher, 2011)
Link to publisher's homepage at http://sciacademypublisher.com